STUDI PERILAKU LEKATAN ANTARA BETON DAN NATURAL FIBER REINFORCED POLYMER (NFRP) DENGAN UJI LEKATAN GESER - Taufiq Saidi; Muhammad Azwar; Muttaqin Hasan; Zahra Amalia (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2022)
Reinforcement and repair of reinforced concrete structures using Fiber Reinforced Polymer (FRP) composites have been widely used. However, the high price is one of the obstacles to applying it. Utilization of natural fiber as a Natural Fiber Reinforced Polymer (NFRP) composite material is an alternative because, in addition to its abundant availability in nature, natural fiber also has low specific gravity, is environmentally friendly, and has a more economical production cost. In this study, natural fibers were used as a substitute for synthetic polymer fibers for strengthening and repairing reinforced concrete structures. This study aims to determine the bond strength between concrete and NFRP. The benefit of this research is to provide an overview of the behavior of the bonding strength of NFRP so that it can be applied to the reinforcement and repair of reinforced concrete structures. The bond strength behavior between concrete and NFRP was tested experimentally. The parameters used were the type of natural fiber (abaka, ramie, pineapple, Samia's silk), the type of adhesive (epoxy, polyester, thixotropic epoxy), and the number of layers of fiber. The test object used the form of a beam (100x100x300) mm and has a single reinforcement of 10 mm in the middle of the cross-section. The width of the NFRP is 50 mm with a bond length of 120 mm. Strain gauges are used on NFRP every 50 mm. In addition, strain gauges are also installed on reinforcement and concrete. A result, NFRP bonding can increase the tensile strength capacity of reinforced concrete beams. Bonding of type-b abaca fiber composite with polyester adhesive is the composite that gives the most significant increase in tensile strength capacity. The Beams with three-layer type-b abaka composite bonded with polyester adhesive experienced the highest increase in tensile strength capacity reaching 47.25%. The results of this study indicate the potential of NFRP as a retrofitting method and further research is needed so that it can be applied to reinforced concrete structures.